2016
DOI: 10.1002/jbio.201600122
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional mapping of the orientation of collagen corneal lamellae in healthy and keratoconic human corneas using SHG microscopy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.Keratoconus is an eye disorder that causes the cornea to take an abnormal conical shape, thus impairing its refractive functions and causing blindness. The late diagnosis of keratoconus is among the principal reasons for corneal surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…In particular, collagen I and collagen II have been proven to efficiently produce SHG signals . SHG has been applied to investigate rat and human corneal samples . Collagen fibrils in cornea were observed under SHG microscopy without any labelling.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, collagen I and collagen II have been proven to efficiently produce SHG signals . SHG has been applied to investigate rat and human corneal samples . Collagen fibrils in cornea were observed under SHG microscopy without any labelling.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, direct evidence for collagen fiber change has been the differing distribution of collagen orientation as observed by the synchrotron X-ray scattering pattern4 and the quantitative analysis of collagen lamellae in keratoconus, as observed by harmonic generation imaging microscopy 5. Marcatelli et al17 reported that the orientation of sutural lamellae close to Bowman’s membrane is significantly different between healthy and keratoconic samples. This suggests that the collagen structure in the keratoconic cornea differs greatly from that in the normal cornea.…”
Section: Discussionmentioning
confidence: 99%
“…NLO measurements were performed using a custom-made laser-scanning nonlinear microscope, originally developed by Cicchi R. et al for biological applications at INO-CNR [10]. The excitation source is a mode-locked Ti:Sapphire laser (Mira 900 F, Coherent Inc., Santa Clara, CA, US).…”
Section: Measurementsmentioning
confidence: 99%
“…In Two-Photon-Excited Fluorescence (TPEF) the detection of fluorescence emitted after the simultaneous absorption of two infrared photons [9] yields to the identification of chromophores. Finally, fluorescence lifetime imaging microscopy (FLIM) measures time-decay of the fluorescence intensity exhibited by fluorescent emitting molecules [10], yielding information on the molecular microenvironment of a molecule and on its energy exchanges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation